Evaluation of The Impact of The Full Systemic Land Registration Policy Implementation in Baubau City - Zainul Abidin (Universitas Medan Area, 2022)
This article intends to evaluate the impact of implementing a full systematic land registration program in Baubau City. With this aim, the researcher used the policy evaluation theory of Wahab as a tentative reference. This research was designed as a qualitative policy evaluation with a formal approach where the assessment used a descriptive approach to produce valid information. The research data was obtained by interviewing the main informants supported by the results of observations and documentation studies and analyzed qualitatively. The data analysis used was an interactive analytical model which included data reduction, data presentation, conclusions, and verification. This research concludes a full systematic land registration program has an impact on the government and society. The government can map plots of land and citizens have legal certainty overland through land certificates, land separation for heirs, and land certificates which are used as business collateral through banking. A full systematic land registration program is also able to reduce the number of overlapping or litigation lands. Implementers and policy planners in the future must pay attention to the input that there needs to be assistance after the community has obtained a certificate so that the land certificate is not used for productive activities. To further minimize uncertified land, further coordination with landowners outside Baubau city and local/kelurahan governments could be intensified.